An energy-efficient switching scheme based on a splitting structure. (January 2023) - Cao, Juntao; Liang, Yuhua
Abstract: An energy-efficient switching scheme is proposed for successive approximation register analog-to-digital converters (SAR ADCs). Benefiting from the method based on MSB splitting and LSB splitting capacitor arrays, the total capacitance of DAC is reduced by 87%. Based on the switching method of the proposed scheme, the CDACs feed energy back to the reference power supply during the switching process to reduce energy consumption. And the proposed scheme achieves 99.61% energy saving reduction over the conventional scheme. In addition, adopting the strategy of unilateral switching can greatly reduce the energy consumption of switching driving, and at the same time reduce the complexity of the control logic. Using the LSB splitting capacitive technique, C-2C scheme is adopted without reducing the unit capacitance, which effectively improves the error caused by capacitance mismatch. The strategy of group reset is adopted, and there is no energy consumption during the reset process. The simulation results show that the differential nonlinearity and integral nonlinearity are 0.335LSB and 0.397LSB, respectively.